The influence of family history on learning opportunities of Inuvialuit youth - Salokangas, Raila; Parlee, Brenda (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2009)
In this article we argue that family histories are key to understanding the differential capacities of Inuvialuit youth to learn traditional knowledge and school curricula. Thematic semi-directed interviews were conducted between 2007 and 2009 with three generations of four Inuvialuit families in Tuktoyaktuk (Northwest Territories). Summaries of each family history are presented to help answer two questions: 1) How do individuals negotiate between different ways of learning? and 2) Why do learning opportunities differ across family groups? We discuss the unevenness of learning opportunities as a result of individual choice and aptitude, family, kinship and community influences, and an increasingly globalised society.